Games as a better way in vocabulary retention of year three students in Sekolah Kebangsaan Bumiputera / Lydia Zeta Donald Stavy - Stavy, Lydia Zeta Donald (2015)
Vocabulary retention is the ability to store or remember as many words as possible. In order to enhance the vocabulary retention of the students, there are a few ways to be used in teaching vocabulary. One of the ways is by using games in the vocabulary learning. However, students often forget the meaning of the new words after be taught by their teachers. This study investigates the students’ achievement in pre-test and post-test. The purpose of this study is to investigate a better way to make the vocabulary learning more retainable by using games. All 64 year three students in Sekolah Kebangsaan Bumiputera, Lundu, Sarawak participated in the study. The students were taught in conventional vocabulary learning for the new words in unit 10. After 2 weeks of teaching, a pre-test was carried out. The new vocabulary in unit 11 of the Year Three English textbook was taught. The teaching of the new words in unit 11 was applied with games. Two weeks after the teaching, a post-test was conducted to the students. The main instruments used to obtain the data were vocabulary retention tests. There were two tests namely pre-test and post test. The result and achievement of the students in the pre-test and post-test measured to identify the vocabulary retention of both group. This study shows that the students scored better result in learning vocabulary through games than conventional vocabulary learning. The data revealed that vocabulary retention was more significant in games vocabulary learning than conventional vocabulary learning.